Structural, functional and biophysical characterization of the secreted, β-helical adhesin EtpA of enterotoxigenic Escherichia coli - Schubert, Wolf-Dieter (University of Pretoria, 2024)
Thesis (PhD (Biochemistry))--University of Pretoria, 2024.